Status of Brucellosis in Dairy Cattle of Kapilvastu and Bhaktapur Districts of Nepal - Ghimire, B.; Thapa Chhetri, S.; Khanal, D.R. (Nepalese Veterinary Journal, 2017)
Brucellosis is a zoonotic disease that causes abortion in dairy cattle. To find out its status, serological tests were conducted, during June-July 2013, in 48 sera samples from dairy cattle (23 from Kapilvastu and 25 from Bhaktapur districts) having the recent history of abortion. Out of 48 samples 6 (12.5%) were positive on Rose Bengal Plate Test. Among 6 positive samples, 2 (8.69%) were from Kapilvastu and 4 (16%) from Bhakhtapur. Considering the positive cases of brucellosis in the dairy pocket areas and its threat of transmission to other animals and human, a suitable preventive and control measures including the regular test and segregation of sero-positive animals, effective quarantine, legislative measures and awareness programs for farmers, veterinarian, technicians and stakeholders are recommended.